Recommendations for safe infant sleep (Research, Society and Development, 2021)
Objective: To identify and guide, in the literature, the position that reduces the involvement of Sudden Infant Death Syndrome (SIDS). Methodology: this is an integrative literature review, where a survey was carried out in the following databases: Scientific Electronic Library Online (Scielo), CINAHL, Science Direct, Medline, Latin American and Caribbean Health Sciences (LILACS) ), MedCarib, PAHO, SCOPUS, Wholis and Embase. Using the descriptors “sudden death”, “newborn”, “newborn”, “dornal decubitus”, “ventral decubitus” with the use of the Boolean operators “and” and “or”. Results: After applying the inclusion and exclusion criteria, 14 articles were qualified where 12 guided the supine position as prevention for SIDS. The main mechanisms of injury associated with SIDS are shown to be: the use of mattresses/co-sleeping (21%), exposure to tobacco (18%), soft objects in bed (18%), lateral decubitus (15%) , use of drugs and alcohol during pregnancy (12%) and use of blankets (12%). Discussion: The findings demonstrated the predominance of the supine position as a measure of recommendation and guidance for SIDS prevention. Conclusions: SIDS is possibly underreported and associated with other diagnoses, it is recommended that health professionals insist and encourage mothers to put the newborn to sleep in the supine position, in order to prevent SIDS.